Low frequency of Plasmodium falciparum hrp2/3 deletions from symptomatic infections at a primary healthcare facility in Kilifi, Kenya - Okanda, Dorcas; Ndwiga, Leonard; Osoti, Victor; Achieng, Nicole; Wambua, Juliana; Ngetsa, Caroline; Lubell-Doughtie, Peter; Shankar, Anuraj; Bejon, Philip; Ochola-Oyier, Lynette Isabella (Frontiers in Epidemiology, 2023)
There is a growing concern for malaria control in the Horn of Africa region due to the spread and rise in the frequency of Plasmodium falciparum Histidine-rich Protein (hrp) 2 and 3 deletions. Parasites containing these gene deletions escape detection by the major PfHRP2-based rapid diagnostic test. In this study, the presence of Pfhrp2/3 deletions was examined in uncomplicated malaria patients in Kilifi County, from a region of moderate-high malaria transmission. 345 samples were collected from the Pingilikani dispensary in 2019/2020 during routine malaria care for patients attending this primary health care facility. The CarestartTM RDT and microscopy were used to test for malaria. In addition, qPCR was used to confirm the presence of parasites. In total, 249 individuals tested positive for malaria by RDT, 242 by qPCR, and 170 by microscopy. 11 samples that were RDT-negative and microscopy positive and 25 samples that were qPCR-positive and RDT-negative were considered false negative tests and were examined further for Pfhrp2/3 deletions. Pfhrp2/3-negative PCR samples were further genotyped at the dihydrofolate reductase (Pfdhfr) gene which served to further confirm that parasite DNA was present in the samples. The 242 qPCR-positive samples (confirmed the presence of DNA) were also selected for Pfhrp2/3 genotyping. To determine the frequency of false negative results in low parasitemia samples, the RDT- and qPCR-negative samples were genotyped for Pfdhfr before testing for Pfhrp2/3. There were no Pfhrp2 and Pfhrp3 negative but positive for dhfr parasites in the 11 (RDT negative and microscopy positive) and 25 samples (qPCR-positive and RDT-negative). In the larger qPCR-positive sample set, only 5 samples (2.1%) were negative for both hrp2 and hrp3, but positive for dhfr. Of the 6, 4 had had more than 100 parasites/µl, suggesting true hrp2/3 deletions. These findings revealed that there is currently a low prevalence of Pfhrp2 and Pfhrp3 deletions in the health facility in Kilifi. However, routine monitoring in other primary health care facilities across the different malaria endemicities in Kenya is urgently required to ensure appropriate use of malaria RDTs.